Lived Experiences of Ghanaian Women With Obstetric Fistula - Mwini-Nyaledzigbor, P.P.; Agana, A.A.; Pilkington, F.B. (Health Care for Women International, 2013)
Obstetric fistula is a worldwide problem that is devastating for women. This qualitative descriptive study explores the experiences of Ghanaian women who sustained obstetric fistula during childbirth. In-depth interviews were conducted with 10 participants. The resultant themes include cultural beliefs and practices surrounding prolonged labor in childbirth, barriers to delivering at a health care facility, and the challenges of living with obstetric fistula, including psychosocial, socioeconomic, physical, and health care access issues. Recommendations include strategies to address this complex problem, including education of men and women on safe motherhood practices, training of traditional birth attendants (TBAs), and improving access to health care. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Ghanaian women; Ghana; obstetric fistula